The Strategy of the Head of Madrasah in Shaping the Quality of Student Tahfidz - Faridah, Ai; Asy’ari, Hasyim (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
. This study uses qualitative research with a case study approach. The object of this research was carried out at MA Plus Al Hikam Sumedang. Data collection techniques using observation, interviews, and documentation. Sources of data in this study included the head of the Madrasah, the coordinator of the tahfidz field, the teacher's council, and one of the students. The analytical techniques used in this study are data collection, data reduction, data presentation, and conclusion. The triangulation used to test the validity of the data is technique and source triangulation. The results of the study revealed the findings that (1) the strategy of the head of the madrasa in shaping the quality of tahfidz students at MA Plus Al Hikam Sumedang designed the tahfidz program to become local content learning, students participated in the tahfidzul Qur'an program to make educational institutions Islamic, superior and ideal, determining target memorization and schedule of tahfidz al-qur'an activities for students. In addition, implementing the tahfidz al-Qur'an program uses a target system of one page in one deposit by memorizing at least five juz for one year. Students use the talaqiq method in memorizing the Qur'an, and students memorize five juz as an obligation in carrying out the Kubro exam. (2) The results of evaluating the quality of tahfidz for MA Plus Al-Hikam students can maintain public trust in madrasas, as one of the leading activity programs in each of these madrasas and students are always able to read and memorize the Qur'an properly and correctly under the rules of reading the Koran, and can make the Koran as a guide in his life.